MODIFIKASI DREDGED NET UNTUK PENINGKATAN EFEKTIVITAS DAN EFISIENSI PENANGKAPAN UDANG DI TAMBAK LOROK, SEMARANG - Aristi Dian P.F; Pramonowibowo Pramonowibowo; Faik Kurohman; Bogi Budi J (Buletin Oseanografi Marina, 2011)
Abstract             Dredged net  was a fishing gear in coastal areas of the dredged (mouth) and bag. Target catch dredged net in the waters Tambak Lorok was shrimp (crustacean). Dredged net  problem that exits due to the large hydrostatic pressure, and number of crew (ABK) a lot and still a chance that the capture of clams can be said to be non selective fishing gear. Aimed of dredged net modifications at improving the effectiveness and efficiency of the caught which would affect the welfare of fishermen, as well as making selective fishing gear through extension activities and training and mentoring             Modifications dredged net is located at the bottom of the mouth of the tool was originally made ​​of tooth-shaped bales iron into iron chains. Analysis of the technical effectiveness and efficiency of the caught showed that dredged net modifications better than the genenui dredged net.   Keywords: Dredged net modification, effective and efficiency